RISK FACTORS ON CARPAL TUNNEL SYNDROME AMONG FURNITURE MAKERS AT HOME INDUSTRIES IN DUREN SAWIT, 2020 - Rahmanndani, Alia (Health Safety Environment, 2020)
Furniture workers are at risk experiencing CTS because it involves using hands to operate hand-tools and machinery and do work manually for a long time without using Personal Protective Equipment (PPE) in the form of gloves that comply with standards. This study aimed to analyze the association between working duration, use of PPE, and intensity of machine vibration exposure with CTS at home furniture industry maker in Duren Sawit, 2020. This research method was a quantitative analytic with a cross-sectional design. The sampling technique used a total sampling of 57 workers consisting of machine user workers and finishing workers. Chi-Square bivariate tests showed a significant association between working duration (p= 0.002), use of PPE (p= 0.003), and intensity of machine vibration exposure (p= 0.009) with CTS. It is recommended for each home industry furniture to promote a safe workplace and safe work practices, educate the workers about CTS prevention, maintain the hand-tools and machinery to prevent injuries, provide rules regarding the use of PPE, and provide standardized anti-vibration gloves.